The Effect of Capital Structure and ESG on Firm Value with Financial Performance as a Mediating Variable (A Study of Mining Sector Companies Listed on the Indonesia Stock Exchange) - Meli Inayatah; Nuraeni (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The mining industry faces increasing pressure to create sustainable firm value as investors place greater emphasis on financial performance and corporate sustainability. Capital structure decisions and Environmental, Social, and Governance (ESG) practices are therefore considered strategic factors that may shape corporate performance and valuation. This study examines the effects of capital structure and ESG performance on firm value, with financial performance as a mediating variable, among mining companies listed on the Indonesia Stock Exchange during 2021–2023. A quantitative approach with a causal-associative design was employed, and the sample was selected using purposive sampling. Data were analyzed using regression analysis and mediation testing. The findings indicate that capital structure has a negative and significant effect on financial performance, whereas ESG performance has a positive and significant effect on financial performance. However, capital structure, ESG performance, and financial performance have no significant effects on firm value. Financial performance also does not mediate the effects of capital structure or ESG performance on firm value. These findings demonstrate that improvements in financial performance arising from financing decisions and ESG practices do not necessarily translate into higher firm value during the period examined. The study contributes to the literature by clarifying the limited mediating role of financial performance in the relationship between corporate financial and sustainability factors and firm value in the Indonesian mining sector. Practically, the findings highlight the need for mining companies to integrate prudent financing decisions with consistent, long-term ESG strategies when pursuing sustainable value creation.